2006
DOI: 10.1037/0022-0167.53.1.80
|View full text |Cite
|
Sign up to set email alerts
|

The meaning in life questionnaire: Assessing the presence of and search for meaning in life.

Abstract: Counseling psychologists often work with clients to increase their well-being as well as to decrease their distress. One important aspect of well-being, highlighted particularly in humanistic theories of the counseling process, is perceived meaning in life. However, poor measurement has hampered research on meaning in life. In 3 studies, evidence is provided for the internal consistency, temporal stability, factor structure, and validity of the Meaning in Life Questionnaire (MLQ), a new 10-item measure of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

147
3,396
13
110

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,378 publications
(3,903 citation statements)
references
References 83 publications
147
3,396
13
110
Order By: Relevance
“…For example, boredom proneness predicts aggression (Dahlen et al, 2004), but so do frustration (e.g., Miller, 1941) and anger (Maiuro, Vitaliano, & Cahn, 1987). Furthermore, although empirical work has confirmed that boredom involves a sense of meaninglessness (Fahlman, Mercer, Gaskocski, Eastwood, & Eastwood, 2009;Van Tilburg & Igou, 2012), so do sadness and feelings of depression (Steger, Frazier, Oishi, & Kaler, 2006). Likewise, boredom is linked to withdrawal behavior (Geiwitz, 1966), but so is disgust (Harlé, & Sanfey, 2010).…”
Section: How Does Boredom Compare To Other Emotions?mentioning
confidence: 99%
“…For example, boredom proneness predicts aggression (Dahlen et al, 2004), but so do frustration (e.g., Miller, 1941) and anger (Maiuro, Vitaliano, & Cahn, 1987). Furthermore, although empirical work has confirmed that boredom involves a sense of meaninglessness (Fahlman, Mercer, Gaskocski, Eastwood, & Eastwood, 2009;Van Tilburg & Igou, 2012), so do sadness and feelings of depression (Steger, Frazier, Oishi, & Kaler, 2006). Likewise, boredom is linked to withdrawal behavior (Geiwitz, 1966), but so is disgust (Harlé, & Sanfey, 2010).…”
Section: How Does Boredom Compare To Other Emotions?mentioning
confidence: 99%
“…Some 20 scales were identified that measured meaning: the Chinese Cancer Coherence Scale (CCCS) (Chan et al, 2007); the Constructed Meaning Scale (Fife, 1995); the meaning/peace subscale of the Functional Assessment of Chronic Illness Therapy -Spiritual Well-Being Scale (FACIT-Sp) (Canada et al, 2008;Murphy et al, 2010;Peterman et al, 2002); the Illness Cognitions Questionnaire (ICQ) (Evers et al, 2001); the Internal Coherence Scale (ICS) (Kroz et al, 2009); the Life Attitude Profile (LAP)/ Life Attitude Profile -Revised (LAP -R) (Reker, 1992;Reker & Peacock, 1981); the Life Evaluation Questionnaire (LEQ) (Salmon et al, 1996); the Meaning in Life questions (including the Benefit Finding Scale [BFS]) used by Tomich and Helgeson (2002); the Meaning in Life Questionnaire (MLQ) (Steger et al, 2006); the Meaning in Life Scale (MILS) (Jim et al, 2006); the Meaning in Suffering Test (MIST) (Starck, 1983); the Perceived Meanings of Cancer Pain Inventory (PMCPI) (Chen, 1999); the Personal Meaning Profile (PMP) (Wong, 1998); the Positive Meaning and Vulnerability Scale (Bower et al, 2005); the Purpose in Life (PIL) Test (Crumbaugh & Maholick, 1964); the Purposelessness, Understimulation, and Boredom (PUB) Scale (Passik et al, 2003); the Schedule for Meaning in Life Evaluation (SMiLE) (Fegg et al, 2008); the Sense of Coherence (SOC) Scale (Antonovsky, 1993); the Sources of Meaning Profile (SOMP)/Sources of Meaning Profile -Revised (SOMP -R) (Reker, 1996); and the World Assumptions Scale (Janoff-Bulman, 1989). The optimal measure of meaning will vary depending on the purpose and context of the assessment.…”
Section: Meaningmentioning
confidence: 99%
“…However, death-related loss can challenge the orienting system of the bereft leading them to engage in meaning making (Park, 2010; Park & Folkman, 1997). This process entails retaining, reaffirming, revising, and/or replacing elements of the orienting system to develop more nuanced, complex, and useful narratives that accommodate the reality of the loss and its implications for the mourner (Bonanno, Wortman, & Nesse, 2004; Gillies, Neimeyer, & Milman, 2014; MacKinnon et al, 2013; Neimeyer, 2000; Neimeyer & Sands, 2011; Park, 2010; Steger, Frazier, Oishi, & Kaler, 2006). When the bereft make progress in negotiating the effect of the loss on their orienting systems, they have made meaning (Gillies et al, 2014).…”
mentioning
confidence: 99%